THE ANALYSIS OF CONTROL SYSTEMS OF RUBBERMIXING - A. V. Krolivets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Comparison of various control systems of rubbermixing and description of the interrelation of rubbermixer parametres and process of mixture are given in the article.